2006
DOI: 10.1385/ncc:5:2:102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Predictors of In-Patient Mortality After Subarachnoid Hemorrhage

Abstract: Cardiovascular abnormalities are independent predictors of in-patient mortality after SAH. Though these effects may be explained by a reduction in cerebral perfusion pressure or other mechanisms, further research is required to determine whether or not they are causal in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 26 publications
4
47
1
Order By: Relevance
“…Hemorrhagic shock also causes decreased cardiac output, stroke volume and cardiac contractility (±dP/dt) (1)(2)(3). Hypoxia and reperfusion injury result in dysregulation of critical molecular pathways and bioprocesses (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhagic shock also causes decreased cardiac output, stroke volume and cardiac contractility (±dP/dt) (1)(2)(3). Hypoxia and reperfusion injury result in dysregulation of critical molecular pathways and bioprocesses (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Brain natriuretic peptide has also been explored as a marker of cardiac injury in SAH patients, and high BNP at admission as well as high troponin-I on the 3rd day after admission has been found to be associated with increased inpatient deaths. 28 Altogether, the studies so far suggest an association among SAH, complications in the heart and brain, and disturbances of fluid and salt balance. However, according to a literature review on SAH and BNP, only a few studies with a larger number of patients exist.…”
mentioning
confidence: 99%
“…Cardiovascular abnormalities after subarachnoid hemorrhage (SAH) have been shown to be independent predictors for inpatient death. 28 It has also been observed that natriuretic peptides, especially brain natriuretic peptide (BNP), increase in SAH patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…myocardial injury, [9][10][11][12][13][14] and left ventricular (LV) dysfunction, 9,13) occur early in the course of SAH. The pathophysiology of these abnormalities is related to increased sympathetic nervous activity 15) and to increased circulating and local myocardial tissue catecholamines.…”
mentioning
confidence: 99%